Oncolytic activity of reovirus in HPV positive and negative head and neck squamous cell carcinoma - Cooper, Timothy (J Otolaryngol Head Neck Surg, 2015)
BACKGROUND: The management of patients with advanced stages of head and neck cancer requires a multidisciplinary and multimodality treatment approach which includes a combination of surgery, radiation, and chemotherapy. These toxic treatment protocols have significantly improved survival outcomes in a distinct population of human papillomavirus (HPV) associated oropharyngeal cancer. HPV negative head and neck squamous cell carcinoma (HNSCC) remains a challenge to treat because there is only a modest improvement in survival with the present treatment regimens, requiring innovative and new treatment approaches. Oncolytic viruses used as low toxicity adjunct cancer therapies are novel, potentially effective treatments for HNSCC. One such oncolytic virus is Respiratory Orphan Enteric virus or reovirus. Susceptibility of HNSCC cells towards reovirus infection and reovirus-induced cell death has been previously demonstrated but has not been compared in HPV positive and negative HNSCC cell lines. OBJECTIVES: To compare the infectivity and oncolytic activity of reovirus in HPV positive and negative HNSCC cell lines. METHODS: Seven HNSCC cell lines were infected with serial dilutions of reovirus. Two cell lines (UM-SCC-47 and UM-SCC-104) were positive for type 16 HPV. Infectivity was measured using a cell-based ELISA assay 18 h after infection. Oncolytic activity was determined using an alamar blue viability assay 96 h after infection. Non-linear regression models were used to calculate the amounts of virus required to infect and to cause cell death in 50% of a given cell line (EC(50)). EC(50) values were compared. RESULTS: HPV negative cells were more susceptible to viral infection and oncolysis compared to HPV positive cell lines. EC(50) for infectivity at 18 h ranged from multiplicity of infection (MOI) values (PFU/cell) of 18.6 (SCC-9) to 3133 (UM-SCC 104). EC(50) for cell death at 96 h ranged from a MOI (PFU/cell) of 1.02×10(2) (UM-SCC-14A) to 3.19×10(8) (UM-SCC-47). There was a 3×10(6) fold difference between the least susceptible cell line (UM-SCC-47) and the most susceptible line (UM-SCC 14A) EC(50) for cell death at 96 h. CONCLUSIONS: HPV negative HNSCC cell lines appear to demonstrate greater reovirus infectivity and virus-mediated oncolysis compared to HPV positive HNSCC. Reovirus shows promise as a novel therapy in HNSCC, and may be of particular benefit in HPV negative patients.